PENYUSUNAN PERANGKAT PEMBELAJARAN PADA MATERI RUANG LINGKUP BIOLOGI KELAS X SMA - Titin, Titin (Jurnal Pendidikan Matematika dan IPA, 2016)
This research aimed to produce a feasible learning set used on scope biology material in Xth Grade of SMA. The learning set extended over documentary film medium, lesson plan, student worksheet, and evaluation test on scope biology material in Xth Grade of SMA Negeri 1 Sengah Temila. Research menthod was performed with descriptive analysis in the form of validity and learning set effectivity. From the result of the research yielded: learning set in the form of documentary film medium, lesson plan, student worksheet, evaluation test, were feasible to use as leraning set on scope biology material in Xth Grade of SMA Negeri 1 Sengah Temila. The set effectiveness, resulted an average score of study archievement by the amount of 75,78 and as much as 83,37% of students who have been attained their KKM.Keywords: feasible learning, scope of biology, validity, effectivity.